2005
DOI: 10.1529/biophysj.105.062620
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Pulmonary Surfactant Due to Serum-Inhibited Adsorption and Reversal by Hydrophilic Polymers: Experimental

Abstract: The rate of change of surface pressure, pi, in a Langmuir trough following the deposition of surfactant suspensions on subphases containing serum, with or without polymers, is used to model a likely cause of surfactant inactivation in vivo: inhibition of surfactant adsorption due to competitive adsorption of surface active serum proteins. Aqueous suspensions of native porcine surfactant, organic extracts of native surfactant, and the clinical surfactants Curosurf, Infasurf, and Survanta spread on buffered subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
199
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(205 citation statements)
references
References 77 publications
3
199
0
1
Order By: Relevance
“…This function of chitosan closely resembles the effect of nonionic polymers in improving surface activity of therapeutic lung surfactants by inducing large surfactant aggregates (5,6) and hence leads us to consider its potential use as a lung surfactant additive. In this study, the effects of chitosan on surface activity of a dilute therapeutic lung surfactant, BLES (BLES Biochemicals Inc, London, ON, Canada), and on the resistance to albumin-induced inactivation are investigated using a CSD method (18).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This function of chitosan closely resembles the effect of nonionic polymers in improving surface activity of therapeutic lung surfactants by inducing large surfactant aggregates (5,6) and hence leads us to consider its potential use as a lung surfactant additive. In this study, the effects of chitosan on surface activity of a dilute therapeutic lung surfactant, BLES (BLES Biochemicals Inc, London, ON, Canada), and on the resistance to albumin-induced inactivation are investigated using a CSD method (18).…”
mentioning
confidence: 88%
“…Both in vitro (1)(2)(3)(4)(5)(6) and in vivo (7)(8)(9) trials have shown that these nonionic polymers can significantly improve the surface activity of different therapeutic lung surfactants and effectively reverse inactivation due to a variety of inhibitory substances.…”
mentioning
confidence: 99%
“…pBALF preparation was modified after Taeusch et al [55]. In short, three porcine lungs, derived from a local butcher and removed in toto, were each filled with about 0.6 l of cold (4 °C) purified water and gently massaged for about 5 min.…”
Section: Preparation Of Porcine Broncheoalveolar Lavage Fluid (Pbalf)mentioning
confidence: 99%
“…As a secondary consequence of several types of lung injury, inflammation and disruption of the alveolarcapillary barrier lead to the leakage of serum components into the airspaces, which are responsible for a severe inactivation of the biophysical activities of the surfactant complex [18]. Several trials have addressed the potential treatment of ARDS with exogenous surfactant in animal models and patients, but with limited success [19,20].…”
Section: Pulmonary Surfactant Function and Dysfunctionmentioning
confidence: 99%
“…Phospholipids constitute around 80% per mass of surfactant and are the main surface active molecules, able to form interfacial films capable of reducing the surface tension at the alveolar air-liquid interface until values close to 0 mN/m, which are reached at the end of expiration, a strict Another pathology related to pulmonary surfactant dysfunction is ARDS associated with acute lung injury (ALI) [17]. As a secondary consequence of several types of lung injury, inflammation and disruption of the alveolarcapillary barrier lead to the leakage of serum components into the airspaces, which are responsible for a severe inactivation of the biophysical activities of the surfactant complex [18]. Several trials have addressed the potential treatment of ARDS with exogenous surfactant in animal models and patients, but with limited success [19,20].…”
mentioning
confidence: 99%